Constrained-efficient capital reallocation - Lanteri, Andrea and Rampini, Adriano A. (The American: Economic Reviews)
We characterize efficiency in an equilibrium model of investment and capital reallocation with heterogeneous firms facing collateral constraints. The model features two types of pecuniary externalities: collateral externalities, because the resale price of capital affects collateral constraints, and distributive externalities, because buyers of old capital are more financially constrained than sellers, consistent with empirical evidence. We prove that the stationary equilibrium price of old capital is inefficiently high because the distributive externality exceeds the collateral externality, by a factor of two when we calibrate the model. New investment reduces the future price of old capital, providing a rationale for new-investment subsidies.- Reproduced